DISTANCE EDUCATION AT THE POSTGRADUATE STAGE OF DOCTOR EDUCATION: PROBLEMS AND THEIR SOLUTIONS AT THE PRESENT STAGE - Mintser, O.P.; Potyazhenko, M.M.; Bumblite, I.A.; Nevoit, G. V.; Bakhanovas, P. O. (Medical Informatics and Engineering, 2023)
Background. The key problematic issues of distance education at the post-graduate stage of training of doctors are analyzed. It is emphasized that working out the methodology of training medical specialists in the online format is very relevant and should be constantly improved. Materials and methods. Results. The purpose of this work was to identify the key problematic issues of distance education at the post-graduate stage of training of doctors and to develop directions for their potential effective solution. The main problematic issues of distance education at the post-graduate stage of training of doctors have been identified. It is proposed to increase the video visualization of all methods and activities that take place in hospitals during the treatment of patients, to create updated methodical support specifically for online classes in the form of additions to existing similar classes or separate methodical developments. Conclusions. Three main problematic issues of distance education at the post-graduate stage of training of doctors have been identified, namely: 1) the impossibility of adequately performing clinical work with patients as the main medical competence; 2) the difficulty of forming systemic medical knowledge as modern professional competence; 3) issues of technical support and quality of video content of visual materials to ensure the distance learning process.